2002
DOI: 10.1093/clinchem/48.6.850
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of Plasma Cystatin C as a Glomerular Filtration Marker in Decompensated Liver Cirrhosis

Abstract: Background: Plasma creatinine concentration and calculated creatinine clearance are of limited value as glomerular filtration rate (GFR) markers in patients with decompensated liver cirrhosis. We assessed plasma cystatin C as an indicator of GFR in such patients. Methods: We studied 36 patients with decompensated liver cirrhosis and 56 noncirrhotic controls, both groups including individuals with normal and impaired renal function. GFR was measured in all individuals by inulin clearance, with va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(57 citation statements)
references
References 19 publications
2
53
0
1
Order By: Relevance
“…8 © 2007 The Japan Society of Hepatology Orlando et al compared cystatin C with serum creatinine in decompensated cirrhotic patients and used inulin clearance to measure GFR. 9 In 36 decompensated post-viral cirrhotic patients, cystatin C was the most sensitive indicator of a low GFR in cirrhotic patients. There were no differences between the reciprocals of cystatin C and serum creatinine and it was suggested that this may relate to the methodology of creatinine measurement; enzymatic PAP method as opposed to the less accurate Jaffe reaction.…”
Section: Cystatin Cmentioning
confidence: 97%
“…8 © 2007 The Japan Society of Hepatology Orlando et al compared cystatin C with serum creatinine in decompensated cirrhotic patients and used inulin clearance to measure GFR. 9 In 36 decompensated post-viral cirrhotic patients, cystatin C was the most sensitive indicator of a low GFR in cirrhotic patients. There were no differences between the reciprocals of cystatin C and serum creatinine and it was suggested that this may relate to the methodology of creatinine measurement; enzymatic PAP method as opposed to the less accurate Jaffe reaction.…”
Section: Cystatin Cmentioning
confidence: 97%
“…32 Based on the inaccuracy of serum Cr, different Cr-based mathematical equations have been used, particularly the MDRD formula. Serum CysC has been considered a more sensitive indicator of renal function, compared to serum Cr, in cirrhosis, [33][34][35] and thus cystatin-based GFR formulae (e.g. Hoek and Larsson) have been proposed.…”
Section: Figurementioning
confidence: 99%
“…Indeed, cystatin C may give similar or more information, compared to Cr. 54,55 In cirrhotics with HRS, cystatin C is at least as accurate as Cr. 56 In a recent study, Gerbes et al evaluated 97 patients and concluded that cystatin C is a useful tool for renal function assessment, especially in patients with endstage liver disease, in women and for earlier diagnosis of renal impairment, compared to enzymatic Cr and C-G formula.…”
Section: Alternative Serum Markers For Assessment Of Renal Functionmentioning
confidence: 99%